2012
DOI: 10.1515/hsz-2011-0247
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of RNA damage under oxidative stress in Escherichia coli

Abstract: We have examined the level of 8-hydroxyguanosine (8-oxo-G), an oxidized form of guanosine, in RNA in Escherichia coli under normal and oxidative stress conditions. The level of 8-oxo-G in RNA rises rapidly and remains high for hours in response to hydrogen peroxide (H2O2) challenge in a dose-dependent manner. H2O2 induced elevation of 8-oxo-G content is much higher in RNA than that of 8-hydroxydeoxyguanosine (8-oxo-dG) in DNA. Under normal conditions, the 8-oxo-G level is low in RNA isolated from the ribosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 49 publications
2
77
0
Order By: Relevance
“…We found that the basal levels of 8-oxo-G on the RNA pool were about three times higher than the levels of 8-oxo-dG on DNA (Figure 5B). In addition, the RNA pool showed increased 8-oxo-G content in all treatment conditions ranging from a 113% increase with Kan to a 175% increase with Amp; the H 2 O 2 positive control (Liu et al, 2012) had the largest increase at 478%.…”
Section: Resultsmentioning
confidence: 97%
“…We found that the basal levels of 8-oxo-G on the RNA pool were about three times higher than the levels of 8-oxo-dG on DNA (Figure 5B). In addition, the RNA pool showed increased 8-oxo-G content in all treatment conditions ranging from a 113% increase with Kan to a 175% increase with Amp; the H 2 O 2 positive control (Liu et al, 2012) had the largest increase at 478%.…”
Section: Resultsmentioning
confidence: 97%
“…First, nucleic acids act as a target for ROS-induced damage causing strand breaks, mutagenesis, and modification of nucleotide bases [3, 78, 79]. Indeed, components of the DNA repair machinery, such as recA , lexA , and sulA appear to be of high importance for virulence and ROS tolerance in S .…”
Section: Damage Repairmentioning
confidence: 99%
“…Indeed, components of the DNA repair machinery, such as recA , lexA , and sulA appear to be of high importance for virulence and ROS tolerance in S . Typhimurium [79-82]. In S .…”
Section: Damage Repairmentioning
confidence: 99%
“…Ribosomal RNA (rRNA) is generally thought to be a poor target, given its complexity of folding and association with ribosomal proteins; however, under oxidative stress conditions, this may not be the case. In contrast to measurements under normal conditions, where 8-oxoG from rRNA is lower compared with that of total RNA, after treatment with H 2 O 2, rRNA oxidation in E. coli correlated with the amount of 8-oxoG in the cell [62, 63]. The effects of oxidative stress on rRNA have also been observed in regions of the brain affected by AD.…”
Section: The Effect Of Rna Damage On Functionmentioning
confidence: 99%